Biodiversity patterns of wetland macroinvertebrate assemblages in the South-Western Cape, South Africa - Mlambo, Musa (University of Cape Town, 2014)
Includes bibliographical references (p. 98-108). === Despite the recent surge in interest in wetland invertebrates, given their immediate importance in overall wetland functioning, these studies have largely been conducted in the northern hemisphere and very little is known in South Africa. In order to fill this knowledge vacuum, this study was conducted to investigate biodiversity patterns of wetland macro invertebrates assemblages in the south-western Cape, South Africa. 140 wetlands were sampled in four geographic clusters, the Cape Flats, the West Coast, the Cederberg and the Agulhas Plain. Open-water, submerged vegetation and emergent vegetation habitats were sampled separately using a square-framed sweep net with a 23.5cm mouth and 80l1m mesh and physico-chemical attributes measured at each site. A total of 126 taxa emanating from more than 26 000 individuals representing 73 genera and 51 families was recorded. Currently, five species new to science were also discovered, three from Hydraenidae (Prosthetops sp. nov, Parhydraena sp. nov and Mesoceration repandum Perkins, 2009), Hydryphantidae (Hydryphanres sp. nov) and Streptocephalidae (Streptocephalus sp. nov). However, all of these new species but one were recorded from single location, suggesting that they might be rare or unique. Richness estimators predicted true taxon richness at about 20-47 taxon more than the observed taxon richness. The high number of uniques and singletons, as well as the Incidence-based Coverage Estimator, suggest that sampling was not adequate to capture the full biodiversity suite. However, I believe this is not necessarily true and this is discussed in detailed in the discussion. The sub-area Cederberg was found to be the biologically richest area, with the three of the new species recorded there. A significant difference was observed in relative abundance (RA) and frequency of occurrence between open-water habitat and vegetated habitats (submerged and emergent vegetation). On the other hand, a significant difference was not found between wetlands with different number of habitat types. No appreciable congruence was seen between different taxonomic groups (i.e. at order and family level) themselves, suggesting that neither can be used as a surrogate for the others. However, predators - which by the way had the highest frequency of occurrence and 2nd highest relative abundance after gatherers - were strongly correlated with overall assemblage and Hemiptera. In addition, together with Hemiptera they had ≥75% similarity with the overall assemblage, suggesting that they are fairly good surrogates for overall assemblage. These results are quite promising especially for biomonitoring programmes and warrant further research. Environmental variables contributed significantly higher in explaining assemblage composition, and the model containing pH, Phosphate, conductivity, turbidity and ammonium was found to explain significant variation in macro invertebrate assemblage.